PERTANGGUNGAN JAWABAN PERDATA OLEH PIHAK ASURANSI TERHADAP KEHILANGAN KENDARAAN YANG MASIH MENJADI TANGGUNGAN PIHAK ASURANSI - Joni Sinatra (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
AbstrackIn Indonesia the use of production technology in the rapid conveyance once, despite these productions which enjoy only partial segments of society alone. Production of motor vehicles is currently not spelled out the amount due to price competition and quality of private vehicles and conveyances public passengers, whether by land, sea or air, the amount of production is increasing from year to year of course have an impact that must be reckoned one of them is from the sector economy. Therefore, various companies have emerged, particularly companies related to the activities of guarantee or tangungan to a person or to a particular asset, because the standard time can be overwritten by a loss or events.